Comparative efficacy analysis identifies immune checkpoint blockade as a new survival benchmark in advanced cutaneous squamous cell carcinoma. (July 2022) - Petzold, Anne; Steeb, Theresa; Wessely, Anja; Schatton, Tobias; Berking, Carola; Heppt, Markus V.
Abstract: Background: Cutaneous squamous cell carcinoma is a common type of skin cancer that may progress to locally advanced or metastatic disease. Both disease stages are managed by a variety of treatment options, including immune checkpoint blockade (ICB), targeted therapy to epidermal growth factor, chemotherapy or treatment combinations. However, the comparative efficacy of such treatments is unclear. Methods: We performed a systematic literature search of Medline, Embase and Central to identify eligible studies reporting Kaplan–Meier curves or individual patient data for overall survival (OS) or progression-free survival (PFS). Kaplan–Meier curves were digitised using the "'WebPlotDigitizer" program. Individual patient data was subsequently remodelled and pooled for distinct treatment groups. Results: Overall, 22 independent studies were included of which n = 927 patients were evaluable for PFS and n = 1054 for OS. ICB showed the highest median PFS (mPFS 9.9 months (95% CI: 8.1–19.9)) and median OS (mOS not reached (95% CI: 31.5 months-not reached)) compared to chemotherapy (mPFS 3.0 months (95% CI: 2.2–4.8), mOS 12.6 months (95% CI: 9.6–15.8)), targeted therapy to epidermal growth factor (mPFS 4.9 months (95% CI: 4.4–5.6), mOS 12.7 months (95% CI: 11.9–14.9)) and combination therapies without ICB (mPFS 9.1 months (95% CI: 8.0–12.1), mOS 18.1 months (95% CI: 16.3–22.8)). The survival benchmark with ICB after 26 months for metastatic squamous cell carcinoma was 70.8% (95% CI: 61.5%–81.5%) versus 37.9% (95% CI: 29.5%–48.8%) for the combination group and 17.1% (95% CI: 9.5%–30.8%) for chemotherapy. Conclusion: ICB is superior to other systemic treatments and sets a novel survival benchmark for advanced cutaneous squamous cell carcinoma. Highlights: The relative efficacy of treatments for cutaneous squamous cell carcinoma is unclear. Immune checkpoint blockade is superior to other systemic treatments. Immune checkpoint blockade sets a new survival benchmark.